Vertical partial laryngectomy for glottic cancer; report of three cases - Raja Lope Ahmad, Raja Ahmad Al'konee; Wan Leman, Wan Ishlah; Kamarudin, Norie Azilah (Faculty of Medicine, International Islamic University Malaysia, 2006)
The ultimate goal of treatment of glottic malignancy is eradication of the cancer regardless of the tumor stage to gain a good local control and preservation of maximum function ideally this would be return of normal speech, respiration and deglutition. The foundation of organ preservation surgery (OPS) is based on the knowledge of laryngeal anatomy and an understanding of how cancers invade the larynx. The organ preservation surgery of the cancer of the vocal cord is based on oncological sound principles, which will be further disscussed in this article. In this article we briefly presented 3 of our cases that underwent vertical partial laryngectomy (VPL) for glottic cancer.